Efficacy of industrial-grade infrared noncontact temperature recording device for fever screening during coronavirus pandemic - Kaminder Bir Kaur; Anuj Singhal; Arun Kumar Yadav; Vishal Mangal; Rohit Jain; Satish Kumar (Wolters Kluwer Medknow Publications, 2020)
Background: The World Health Organization declared COVID-19 "a pandemic" on March 11, 2020. An essential preventive and screening strategy adopted was temperature screening at various public places such as airports and hospitals with devices like handheld, noncontact infrared thermometers. Before this pandemic, the industrial thermometers have never been used in health-care settings. The study was conducted to compare temperature readings of these industrial-grade infrared noncontact handheld thermometers with a digital thermometer. Materials and Methods: Three Testo® industrial-grade infrared noncontact thermometer (IGNCT) and Dr. Trust digital thermometer were used on 117 individuals for recording temperature. The average of three readings was taken for each instrument by a single investigator. Results: Out of 117 individuals, 14 (11.9%) were febrile. The Pearson correlation values between the digital thermometers varied from 0.3 to 0.42. The reliability, as measured by the intraclass correlation, was poor (0.16-"0.4). The area under the curve for IGNCT devices varied from 76% to 84%. Conclusion: Industrial-grade infrared noncontact temperature (IGNCT) recording devices with its no-touch technique to measure temperature while maintaining distance may be useful in a pandemic situation. However, the higher the area under the curve, the better it is. In a large cohort, 20% will be misclassified, and in absolute terms, they may be translated into large numbers. Hence, there is a case for better devices having an area under the curve of nearly 100% for the screening of population. The role of IGNCT devices for the screening of individuals to identify cases of febrile illness is limited owing to its poor reliability and unacceptable area under the curve for screening large populations.